Indonesian Learning Management Based UASBN (A Site Study at SDN Jurangombo 4 Magelang) - Zulaeni, Zulaeni (2011)
The objectives of this research are to describe (1) Characteristics of National Standard Final Exam (UASBN)-Based Indonesian learning material at SDN 4 Magelang, (2) characteristic of National Standard Final Exam (UASBN)-Based Indonesian learning material at SDN 4 Magelang, and (3) Characteristic of National Standard Final Exam (UASBN)-Based Indonesian learning evaluation at SDN 4 Magelang. This is qualitative research conducted in SDN Jurangombo 4 Magelang. The main subjects in this research are school principals and teachers. Data collection techniques used in this research is in depth interview, observation and documentation. The data analysis techniques in this research are build an explanation, entering data, and analyzing data. The validity of the data in this study carried out by triangulation. Research's results showed that (1) Implementation of the learning is accordance to the KTSP curriculum and UASBN signs. An Indonesian subject is beginning with the planning implementation of the learning subject matter that will be delivered. Indonesian language teaching material is taught in VI class includes listen, speak, write and read. From the fourth Indonesian language teaching materials that are taught is only two subject's matter that is subject matter that is read and writes in exams. Subject matter of write was conducted over two meetings of 4x35 minutes. (2) In the process of teaching and learning in the classroom is supported by the methods used by teachers. The method used by teachers in elementary school state Jurangombo 4 Magelang is PAKEM method (active learning creative), which consists of asked questions method, discussion, assignment, or multi-method. Teaching methods that used by teachers in learning of Indonesian based UASBN is also done through the addition of lessons hours. (3) In Indonesian language subject, the evaluation is done by oral and written evaluation. Learning evaluation conducted in three stages: evaluation before class, evaluation during the process and evaluation at the end of the lesson. Teachers also conduct an overall evaluation of activities conducted at the Midterm Test (UTS) and Final Test (UAS), Final Examination; National Standard Final Exam (UASBN) that will determine students' graduation from elementary school. Before doing UAS, school is doing pre UAS that is done one month before the Final Examination Schools.